Pre-surgical mapping of eloquent cortex for paediatric epilepsy surgery candidates: Evidence from a review of advanced functional neuroimaging. (November 2017) - Collinge, Sarah; Prendergast, Garreth; Mayers, Steven T.; Marshall, David; Siddell, Poppy; Neilly, Elizabeth; Ferrie, Colin D.; Vadlamani, Gayatri; Macmullen-Price, Jeremy; Warren, Daniel J.; Zaman, Arshad; Chumas, Paul; et al.
Highlights: A systematic review has not been published before. 34 papers met inclusion criteria with 353 paediatric participants identified. PPV 74% (95% CI 61–87) and NPV 65% (95% CI 52–78) for fMRI language were obtained. It remains unclear which language paradigms produce optimal activation. Paradigms and analyses concordant with independent measures are needed. Abstract: Purpose: A review of all published evidence for mapping eloquent (motor, language and memory) cortex using advanced functional neuroimaging (functional magnetic resonance imaging [fMRI] and magnetoencephalography [MEG]) for paediatric epilepsy surgery candidates has not been conducted previously. Research in this area has predominantly been in adult populations and applicability of these techniques to paediatric populations is less established. Methods: A review was performed using an advanced systematic search and retrieval of all published papers examining the use of functional neuroimaging for paediatric epilepsy surgery candidates. Results: Of the 2724 papers retrieved, 34 met the inclusion criteria. Total paediatric participants identified were 353 with an age range of 5 months-19 years. Sample sizes and comparisons with alternative investigations to validate techniques are small and variable paradigms are used. Sensitivity 0.72 (95% CI 0.52–0.86) and specificity 0.60 (95% CI 0.35–0.92) values with a Positive Predictive Value of 74% (95% CI 61–87) and a Negative Predictive Value of 65% (95% CI 52–78) for fMRI language lateralisation with validation, were obtained. Retrieved studies indicate evidence that both fMRI and MEG are able to provide information lateralising and localising motor and language functions. Conclusions: A striking finding of the review is the paucity of studies (n = 34) focusing on the paediatric epilepsy surgery population. For children, it remains unclear which language and memory paradigms produce optimal activation and how these should be quantified in a statistically robust manner. Consensus needs to be achieved for statistical analyses and the uniformity and yield of language, motor and memory paradigms. Larger scale studies are required to produce patient series data which clinicians may refer to interpret results objectively. If functional imaging techniques are to be the viable alternative for pre-surgical mapping of eloquent cortex for children, paradigms and analyses demonstrating concordance with independent measures must be developed.